MODEL GRAVITASI INTERAKSI PERDAGANGAN INDONESIA DENGAN MALAYSIA DAN SINGAPURA - martin Luter purba; demak sinta buulolo (Journal of Economic and Business, 2020)
This study aims to look at the impact of interactions (gravity method) in explaining the trade relations between two countries. This study uses a different test, a dummy variable regression and VAR models to see the response of the shocks to the interaction of the gravity method. The data used starts from 2010 to 2018. The results show the gravity method can explain the trade relationship between Indonesia and Malaysia and Singapore. Indonesian exports to Malaysia respond negatively to interaction shocks while to Singapore to interaction shocks respond positively. Besides interactions, the AEC which began in 2016 also influenced the volume of Indonesian exports to Malaysia and Singapore.